94.8k views
5 votes
If f(x) = x^3 – x^2 – 3, which of the following is equal to g(x) = f(2 – x)?

–x^3 + 5x^2 – 8x + 1
–x^3 + 7x^2 – 16x – 15
x^3 + 5x^2 + 8x + 1
x^3 – 7x^2 + 16x – 15

User Gyohza
by
5.6k points

1 Answer

3 votes

Answer:

–x^3 + 5x^2 – 8x + 1

Explanation:

You can observe that expanding f(2-x) will give you a sum that includes (2-x)³, so will have a -x³ term. This narrows the choices to one of the first two.

If x=0, then you have ...

... f(2) = 2^3 -2^2 -3 = 8 - 4 - 3 = 1 . . . . corresponds to the first selection

_____

Worked in detail

f(2-x) = (2-x)³ -(2-x)² -3 . . . . substitute 2-x for x in the expression for f(x)

... = (2³ -3·2²x +3·2x² -x³) -(2² -2·2x +x²) -3

... = -x³ +5x² -8x +1 . . . . . matches the first selection

_____

Using ...

... (a+b)³ = a³ + 3a²b +3ab² +b³

... (a+b)² = a² +2ab +b²

User Andres D
by
6.2k points